Sickness absence and local benefit cultures - Assar Lindbeck; Mårten Palme; Mats Persson (Institute for the Study of Labor (IZA), 2011)
In many countries, sickness absence financed by generous insurance benefits has become an important concern in the policy debate. It turns out that there are strong variations in absence behavior between local geographical areas, and it has been difficult to explain these variations by observable socioeconomic factors. In this paper we investigate whether such variation is related to group effects in the form of social interaction among individuals within neighborhoods. Well-known methodological problems arise when trying to answer such a question. A special feature of our attempt to deal with these problems is that we adopt several alternative approaches to identify group effects. We base the study on a rich set of Swedish panel data, and we find indications of group effects in each one of our approaches.
urn:nbn:de:101:1-201203014815
Keywords: H56; I38; J22; Z13; 330; sick-pay insurance; work absence; moral hazard; reflection problem; social norms; Lohnfortzahlung; Fehlzeit; Moral Hazard; Regionale Disparität; Soziale Beziehungen; Panel; Schätzung; Schweden